The Teddy Bear's: Have a dream. (Montreal, Canada : Tormont Publication Inc, 1992)
It is a warm, moonlit night. The three bears, Ragtime, Tatty Ted and BB are very sleepy. Tatty Ted looks up at the stars and starts to dream.
Keywords: Dreams--Fiction; Bears--Fiction; Children stories